2021
DOI: 10.1097/cad.0000000000001188
|View full text |Cite
|
Sign up to set email alerts
|

LINC00987 knockdown inhibits the progression of acute myeloid leukemia by suppressing IGF2BP2-mediated PA2G4 expression

Abstract: This study aimed to investigate the role and potential mechanisms of LINC00987 in acute myeloid leukemia (AML) progression. The expression of LINC00987 in bone marrow specimens of AML patients and cell lines was measured by quantitative reverse transcription PCR (RT-qPCR). Small interfering RNA targeting LINC00987 (si-LINC00987) was transfected into AML cell lines HL-60 and KG-1, and the proliferation, invasion and apoptosis were detected with Cell Counting Kit-8 (CCK-8), Transwell and flow cytometry, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…LncRNA plays an important role in occurrence, development, and prognosis of AML [22]. Among seven lncRNAs in the prognostic risk model, the lncRNA LINC00987 and MIR133A1HG deregulation were demonstrated signi cantly correlated with prognosis and tumor progression in AML [23,24], indicated that LINC00987 and MIR133A1HG may serve as new promising individualized therapeutic targets for the treatment of AML [25]. Our data rea rmed its potential value as therapeutic targets in AML.…”
Section: Discussionsupporting
confidence: 64%
“…LncRNA plays an important role in occurrence, development, and prognosis of AML [22]. Among seven lncRNAs in the prognostic risk model, the lncRNA LINC00987 and MIR133A1HG deregulation were demonstrated signi cantly correlated with prognosis and tumor progression in AML [23,24], indicated that LINC00987 and MIR133A1HG may serve as new promising individualized therapeutic targets for the treatment of AML [25]. Our data rea rmed its potential value as therapeutic targets in AML.…”
Section: Discussionsupporting
confidence: 64%
“…It can bind YTHDF2 to increase FYN expression and promote hepatocellular carcinoma metastasis [ 42 ]. Moreover, PA2G4 is reported to be regulated by noncoding RNA [ 43 , 44 ]. For example, circERBB2 promotes gallbladder cancer progression by regulating PA2G4‐modulated ribosomal DNA transcription [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, circERBB2 promotes gallbladder cancer progression by regulating PA2G4‐modulated ribosomal DNA transcription [ 43 ]. Knockdown of LINC00987 suppresses acute myeloid leukemia progression by inhibiting the IGF2BP2‐mediated PA2G4 expression [ 44 ]. More importantly, the expression of PA2G4 has been reported to be elevated in NPC and is associated with a poor prognosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs, a novel precision medicine drug class, hold promise to meet this clinical need to selectively inhibit any sequence (including noncoding sequences[6]) in the transcriptome. However, siRNA delivery to immune cells (i.e.…”
Section: Introductionmentioning
confidence: 99%